1978
DOI: 10.2170/jjphysiol.28.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gustatory Stimulants upon the Olfactory Epithelium of the Bullfrog and the Carp

Abstract: Effects of various gustatory stimulants upon the olfactory epithelia were examined in the olfactory bulb of the bullfrog and the carp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…Induced waves and single cell discharges of the olfactory bulb were recorded also by the same procedures as before (TAKAGI et al, 1978a).…”
Section: Methodsmentioning
confidence: 99%
“…Induced waves and single cell discharges of the olfactory bulb were recorded also by the same procedures as before (TAKAGI et al, 1978a).…”
Section: Methodsmentioning
confidence: 99%
“…The water response was also observed in the labellar chemosensory hairs of the fly (Wolbarsht, 1957;Evans & Mellon, Jr., 1962;Rees, 1970). Takagi, Iino & Yarita (1978) found that the water response was also produced by stimulation of the frog olfactory epithelium with distilled water. The present study was undertaken to confirm the water response of the frog olfactory epithelium and to investigate the response characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the effects of ions in various concentrations, 1 M solutions of NaCl, RbCI, Na4Fe(CN)6 or Na2SO4 were diluted by distilled water and 2-1, 2-2, 2-3 ... 2-12 and 2-13 M solutions were prepared. When the effects of the osmotic pressure of the stimulating solutions were examined, isotonic (6 %) sucrose solution which had been found to have no stimulating action by itself (TAKAGI et al, 1978), was used and various hypertonic and hypotonic sucrose solutions were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…HARA and GORBMAN (1967) disclosed in the goldfish that a similar rhythmic wave is induced in the olfactory bulb by a sodium chloride solution which is applied to the olfactory epithelium. In a previous paper (TAKAGI et al, 1978), it was shown that the olfactory cells are stimulated by many gustatory stimulants except the sweet solutions. In the fish, it was also proven that the olfactory receptor cell is sensitive not only to odors in aqueous phase but also to mechanical stimuli (ADRIAN and LUDWIG, 1938 ;TAKAGI et al, 1978).…”
mentioning
confidence: 98%
See 1 more Smart Citation